CISGENDERITY IN DENIAL: PRESENTING THE CONCEPT OF OFFENSE OF DESIGNATION - Pfeil, Bruno Latini; Pfeil, Cello Latini (Revista de Estudos em Educação e Diversidade - REED, 2022)
In this article, we aim to analyze what we call the “offense of designation”, referring to the set of mechanisms used by cisgender people to deny their cisgender social location. Unlike the terminologies focused on transgenderism, which emerged at the end of the 19th century and gained strength in the 1960s, the concept of cisgenderity emerged only in the last decades of the last century, and has gained strength recently. If transgender was named by cisgender people in a pathologization perspective and with academic institutional contributions, cisgender was named by trans people through a critical lens and in opposition to the gender norms of modernity/coloniality; it is a concept created within social movements, outside the academy. There is a concrete difference between the discourses of trans people and those of cis people about their social belonging, referring us to the refusal, on the part of cis people, to recognize their cisgenderness. In this way, we seek to investigate the obstacles that permeate the application and recognition of the concept of cisgenderism by cisgender people, especially in the academic environment, which is the territory of our research.